DEVELOPMENT OF E-LKPD WORDWALL GAME IN JAVA BANTEN LEARNING FOR CLASS 1 ELEMENTARY SCHOOL : PENGEMBANGAN E-LKPD WORDWALL GAME PADA PEMBELAJARAN JAWA BANTEN SISWA KELAS 1 SD - Avinindy Inayda Devianti -; Aceng Hasani; Aan Hendrayana (Jurnal Cakrawala Pendas, 2024)
Digital technology has now developed rapidly in all aspects of life, including in the aspect of education. The implementation of technology in the world of education is one of the barometers of a nation's progress. However, amidst the demands of the times, Indonesia remains a nation that must maintain its culture, one of which is the regional language of Java Banten. Collaboration of modern developments with culture is a formula that is expected to increase student motivation and learning outcomes. This research is a R&D by adopting the ADDIE model. The objectives of this study are: 1) product design of e-LKPD wordwall game; 2) product eligibility of e-LKPD wordwall game; 3) student responses to the development of e-LKPD; 4) description of increasing student learning motivation in the implementation of e-LKPD wordwall game that can be seen from student responses in using the product; 5) description of increasing student learning outcomes in the implementation of e-LKPD Wordwall game. The analysis technique uses 2 stages (qualitative analysis and quantitative analysis). The results of the validation test of the e-LKPD wordwall game obtained an average score of expert validation 89.53%, student responses to the aspect of using the e-LKPD wordwall game obtained a score of 61%, the aspect of learning motivation obtained a score of 64%, the analysis of student learning outcomes obtained a result of 63% in the moderate criteria and quite effective to use. The conclusion of the results obtained was stated as valid by experts, the effectiveness of the e-LKPD wordwall game was categorized as good and quite effective to use.